Metal-free photo-induced sulfidation of aryl iodide and other chalcogenation - Mao, Shuai; Zhao, Yahao; Luo, Zixuan; Wang, Ruizhe; Yuan, Bo; Hu, Jianping; Hu, Linghao; Zhang, San-Qi; Ye, Xiaoxing; Wang, Mingliang; Chen, Zhengkai (Frontiers in Chemistry, 2022)
A photo-induced C-S radical cross-coupling of aryl iodides and disulfides under transition-metal and external photosensitizer free conditions for the synthesis of aryl sulfides at room temperature has been presented, which features mild reaction conditions, broad substrate scope, high efficiency and good functional group compatibility. The developed methodology could be readily applied to forge C-S bond in the field of pharmaceutical and material science.